Both sedentary time and physical activity are associated with cardiometabolic health in overweight adults in a 1 month accelerometer measurement - Tanja Sjöros; Henri Vähä-Ypyä; Saara Laine; Taru Garthwaite; Minna Lahesmaa; Sanna M. Laurila; Aino Latva-Rasku; Anna Savolainen; Annika Miikkulainen; Eliisa Löyttyniemi; Harri Sievänen; Kari K. Kalliokoski; et al. (Nature Research, 2022)
The aim of this study was to examine the associations of cardiometabolic health markers with device-measured sedentary behavior (SB) duration and different intensities of physical activity (PA) among overweight working-aged adults with low self-reported PA levels. This cross-sectional analysis included 144 subjects (42 men) with mean age of 57 (SD 6.5) years and mean BMI of 31.7 (SD 4) kg/m2. SB and standing time, breaks in sedentary time, light PA (LPA) and moderate-to-vigorous PA (MVPA) were measured for 4 consecutive weeks (mean 25 days, SD 4) with hip-worn accelerometers. Fasting plasma glucose, insulin, HbA1c, triglycerides and total cholesterol, HDL and LDL were measured from venous blood samples. HOMA-IR index was calculated as a surrogate of insulin resistance. The associations were examined using linear models. LPA, MVPA, and daily steps associated with better insulin sensitivity and favorable plasma lipid profile, when adjusted for age, sex and BMI, whereas greater proportion of SB associated with insulin resistance and unfavorable lipid profile. As all PA intensities associated with better cardiometabolic health, the total daily duration of PA may be more relevant than intensity in maintaining metabolic health in overweight adults, if the current guidelines for PA are not met.